2000
DOI: 10.1086/309261
|View full text |Cite
|
Sign up to set email alerts
|

Massive Star Formation and Evolution in Starburst Galaxies: Mid‐infrared Spectroscopy with theISOShort Wavelength Spectrometer

Abstract: We present new ISO-SWS data for a sample of 27 starburst galaxies, and with these data examine the issues of formation and evolution of the most massive stars in starburst galaxies. Using starburst models which incorporate time evolution, new stellar atmosphere models for massive stars, and a starburst model geometry derived from observations of the prototypical starburst M82, we model the integrated mid-infrared line ratio [Ne III](15.6µm)/[Ne II](12.8µm). This line ratio is sensitive to the hardness of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
283
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(325 citation statements)
references
References 95 publications
(119 reference statements)
41
283
1
Order By: Relevance
“…Schaerer 2003). Although Thornley et al (2000) estimate a diffuse contribution to be insignificant, this remains to be demonstrated observationally.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Schaerer 2003). Although Thornley et al (2000) estimate a diffuse contribution to be insignificant, this remains to be demonstrated observationally.…”
Section: Introductionmentioning
confidence: 88%
“…Thornley et al 2000) is not completely clear and has led to somewhat conflicting or inconsistent interpretations. Thornley et al (2000) argue e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thornley et al (2000) used the mid-infrared line ratio of [Ne iii] 15.6/ [Ne ii] 12.8 to measure the hardness of the stellar ionizing radiation. They found that, on average, stars with masses above about 40 M are not present in starburst galaxies, either because they were never formed or because they have already disappeared as a result of aging effects.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this, Thornley et al (2000) carried out detailed starburst modelling of the [Ne III] 15.6 µm / [Ne II] 12.8 µm ratio of H II regions ionized by clusters of stars. As was shown above, the hottest stars in such models are responsible for producing large nebular [Ne III] 15.6 µm / [Ne II] 12.8 µm ratios.…”
Section: Spectral Energy Distributions Of Time-evolving Stellar Clustersmentioning
confidence: 99%